2018
DOI: 10.1007/s10461-018-2255-6
|View full text |Cite
|
Sign up to set email alerts
|

Virological Non-suppression and Its Correlates Among Adolescents and Young People Living with HIV in Southern Malawi

Abstract: We examined virological non-suppression (VLN) among youth ages 13-24 years receiving HIV treatment in public health facilities in six southern Malawi districts. We also tested three ART adherence measures to determine how well each identified VLN: pill counts, a Likert scale item, and a visual analogue scale. VLN was defined as HIV RNA > 1000 copies/ml. Of the 209 youth, 81 (39%) were virally non-suppressed. Male gender and stigma were independently associated with VLN; social support and self-efficacy were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 38 publications
4
51
3
Order By: Relevance
“…Evidence on the relationship between gender and viral load suppression is mixed. While one study showed that males were more likely to achieve viral load suppression compared to females [20], another study found that males are more likely to achieve viral non suppression [24]. However, we found that females were more likely to attain viral suppression compared to males.…”
Section: Discussioncontrasting
confidence: 80%
“…Evidence on the relationship between gender and viral load suppression is mixed. While one study showed that males were more likely to achieve viral load suppression compared to females [20], another study found that males are more likely to achieve viral non suppression [24]. However, we found that females were more likely to attain viral suppression compared to males.…”
Section: Discussioncontrasting
confidence: 80%
“…15,18 The possible reason may be due to fear of disclosure to their family and relatives. 19 So that different study shows that younger age groups are not disclosing their HIV status and disclosure is one of the predictor variable for Virological failure. 20,21 Therefore, health-care providers better provide a patient-centered approach to younger age groups in order to reduce mortality in earlier ages of ART clients and increase productivity at individual and national levels.…”
Section: Discussionmentioning
confidence: 99%
“…Nondisclosure and lack of routine have been identified as contributing to poor medication adherence and retention in care. These factors are compounded by cognitive, emotional, and social changes associated with the transition from childhood to adulthood, as well as stigma surrounding HIV, including within the school environment [7][8][9][10][11][12][13][14]. Support groups have emerged as a feasible strategy, and evidence of their impact on the health and well-being of children, adolescents, and youth is growing [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%